Pengaruh Kepemimpinan Kepala Sekolah Dan Komitmen Terhadap Kinerja Guru SD Negeri Kecamatan Cipeundeuy Kabupaten Bandung Barat - Teti Herawati; Kadir Kadir (Majalah Bisnis & IPTEK, 2019)
Research conducted to determine the effect of principal leadership and commitment on performance of public elementary teachers in Cipeundeuy District, West Bandung Regency. This research conducted in West Bandung Regency Elementary School, where the method used was descriptive and verification methods, with 33 respondents. The data analysis technique used was a path analysis technique to determine the effect of both direct and indirect variables on the dependent variable. In its operation, SPSS 19 and Excel software used. The results of the study showed that leadership was quite a good category. Commitment to the category is quite good, and Teacher performance is in a quite good category. The total effect of leadership on teacher performance is 19.8%; the overall effect of commitment to teacher performance is 31.2%. The simultaneous influence of Leadership and Commitment on the Performance of Public Elementary Teachers in Cipeundeuy Sub-District, West Bandung Regency is 51.0%, and the remaining 49.0% determined by other variables not included in this study.